2017
DOI: 10.21451/1984-3143-ar808
|View full text |Cite
|
Sign up to set email alerts
|

Can feed supplementation of the refined vegetable oils enhance the seminal quality of rabbit bucks (Oryctolagus cuniculus)?

Abstract: Exploring new feeding strategies are a necessary aspect for improving the reproductive performance in rabbits. Twenty healthy rabbit bucks with a mean live body weight of 1.01 kg (SD = 0.12) and age of 6 months old were used for a period of 17 weeks to examine the influence of feeding soybean and sunflower oils on their reproductive performance. Rabbits were randomly assigned into 4 groups (5 bucks/group), where bucks in the 1st group, served as a control, were fed for 14 weeks on a standard ration without any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…On contrary, Okab et al (2017) reported that neither soybean oil nor sunflower oil as sources of (Ω-3-PUFA) with different ratios in rabbit diets had a particular trend of feed conversion ratios calculated for all groups exhibited, to some extent, comparable figures.…”
Section: Growth Measurementsmentioning
confidence: 83%
See 2 more Smart Citations
“…On contrary, Okab et al (2017) reported that neither soybean oil nor sunflower oil as sources of (Ω-3-PUFA) with different ratios in rabbit diets had a particular trend of feed conversion ratios calculated for all groups exhibited, to some extent, comparable figures.…”
Section: Growth Measurementsmentioning
confidence: 83%
“…Also, Delgado (2017) found that linseed oil as a source of fatty acids in rabbit diets improved both LBW and average daily gain. Okab et al (2017), using different sources of Ω-3-PUFA in rabbit diets, found that body weight gain of bucks fed either 3% soybean oil or 1.5% soybean oil + 1.5% sunflower oil showed (P<0.05) increases, whereas no effects (P>0.05) was observed on the bucks fed 3% sunflower oil, compared to bucks in the control group.…”
Section: Growth Measurementsmentioning
confidence: 96%
See 1 more Smart Citation